Optimalisasi Penjadwalan Proyek Menggunakan Metode Time-Cost Trade Off - Tio Boanmora Nabasa Rajagukguk; Lila Ayu Ratna Winanda; Munasih; Sriliani Surbakti (Jurnal Konstruksi, 2026)
Accelerating the duration of construction projects has the potential to increase costs, so an analytical approach is needed to balance time and costs efficiently. This study analyzes the application of the Time–Cost Trade Off (TCTO) method in project scheduling optimization by evaluating the relationship between time acceleration and total cost changes. The study uses data on normal duration and accelerated duration, direct costs, and additional costs due to overtime. The analysis methods include the Critical Path Method (CPM) to identify critical activities and TCTO-based crashing analysis to determine economical acceleration alternatives. The results show that the normal project duration is 151 days with a total cost of IDR 1,634,386,623.07. The application of 2 hours of overtime resulted in a duration of 131 days with a total cost of IDR 1,811,132,883.32, while 3 hours of overtime reduced the duration to 123 days with a total cost of IDR 1,817,213,981.61. These findings indicate that accelerating the project duration has an impact on increasing costs, so the selection of an acceleration scenario needs to consider the trade-off between time reduction and additional costs as the basis for project scheduling decisions.